Association of Vitamin-D Status with Ischemic Stroke and It’s Risk Factors In Bangladeshi Patients: A Case-Control Study (Bangladesh Journal of Medicine, 2023)
Background: Vitamin D (VD) shortage and inadequacy are serious global health issues affecting people of all ages. Several studies have shown a link between VD insufficiency and ischemic stroke. Unfortunately, VD is rarely measured, diagnosed, or treated, especially in patients with severe neurological disorders like stroke in our context. The study aimed to explore the association between VD and the risk of acute ischemic stroke along with its risk factors in Bangladeshi patients.Methods: Forty-four patients with ischemic stroke and 44 age and sex-matched healthy subjects were included in this study from Chittagong Medical College Hospital. Demographic and clinical data were collected with a structured interview questionnaire. Fasting 25(OH) VD, calcium, lipid profile, and blood sugar were measured. VD levels classified the individuals in sufficient (VDSe”30.0 ng/mL), insufficient (VDI: 20.0–29.9 ng/mL), and deficient (VDD